2013
DOI: 10.3389/fnsys.2013.00045
|View full text |Cite
|
Sign up to set email alerts
|

The anterior thalamus provides a subcortical circuit supporting memory and spatial navigation

Abstract: The anterior thalamic nuclei (ATN), a central component of Papez' circuit, are generally assumed to be key constituents of the neural circuits responsible for certain categories of learning and memory. Supporting evidence for this contention is that damage to either of two brain regions, the medial temporal lobe and the medial diencephalon, is most consistently associated with anterograde amnesia. Within these respective regions, the hippocampal formation and the ATN (anteromedial, anteroventral, and anterodor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
190
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(210 citation statements)
references
References 114 publications
8
190
1
3
Order By: Relevance
“…1, top), including three anterior subnuclei (anterodorsal, anteroventral, anteromedial) and two lateral subnuclei (laterodorsal and lateroposterior). Neuroanatomical studies have suggested that subcortical inputs to the thalamus differentiate anterior and lateral subregions (for review see Mizumori et al, 2005 andJankowski et al, 2013; Fig. 1, bottom).…”
Section: Subregions and Connectivitymentioning
confidence: 97%
“…1, top), including three anterior subnuclei (anterodorsal, anteroventral, anteromedial) and two lateral subnuclei (laterodorsal and lateroposterior). Neuroanatomical studies have suggested that subcortical inputs to the thalamus differentiate anterior and lateral subregions (for review see Mizumori et al, 2005 andJankowski et al, 2013; Fig. 1, bottom).…”
Section: Subregions and Connectivitymentioning
confidence: 97%
“…All the aforementioned brain areas share abundant connections with limbic thalamic nuclei (Gabbott et al 2005;Groenewegen 1988;Hoover and Vertes 2007) such as the anterior thalamic nuclei (ATN) and mediodorsal (MD) nuclei. While the ATN is known to support spatial navigation (Jankowski et al 2013;van Groen and Kadish 2002;Warburton et al 1999Warburton et al , 2001Wilton et al 2001;Wolff et al 2008a, b), the role of MD in goaldirected behavior has been the focus of recent studies in essentially non-spatial, instrumental settings (Mitchell et al 2007;Ostlund and Balleine 2008;Pickens 2008). Still few studies have directly compared the differential impact of lesion to either the ATN or the MD on goal-directed behavior and none of them involved processing of spatial information .…”
Section: Introductionmentioning
confidence: 96%
“…Declining memory performance is perhaps the cognitive deficit most commonly associated with advancing age (see Craik & Rose, 2012 and Khan, Martin‐Montanez, Navarro‐Lobato, & Muly, 2014 for reviews). While the hippocampus clearly plays a vital role in explicit (Riedel et al., 1999; Schacter, Alpert, Savage, Rauch, & Albert, 1996; Squire, 1992) and implicit (Duss et al., 2014) memory, the connectivity between the hippocampus and other brain regions, including the anterior thalamus, has also been implicated in supporting memory function (Aggleton & Brown, 1999; Aggleton et al., 2010; Child & Benarroch, 2013; Jankowski et al., 2013). Evidence from patients with thalamic infarcts supports the view that disrupted thalamo‐cortical structural connectivity is associated with memory problems (Serra et al., 2014), while functional connectivity (FC) strength between the dorsomedial nucleus of the thalamus and parts of the striatum has also been negatively associated with episodic memory functioning in 49‐ to 80‐year‐olds (Ystad, Eichele, Lundervold, & Lundervold, 2010).…”
Section: Introductionmentioning
confidence: 99%